Driving immunization through the Medicare Annual Wellness Visit: A growing opportunity. Issue 50 (15th December 2017) - Shen, Angela K.; Warnock, Rob; Kelman, Jeffrey A.
Highlights: The Medicare Annual Wellness Visit (AWV) is an opportunity to educate beneficiaries. Utilization of the AWV has increased over time from 8% in 2011 to 19% in 2015. Vaccination rates are higher among those who utilize the AWV benefit. Abstract: Introduction: The Annual Wellness Visit (AWV) is a Medicare benefit designed to help prevent disease and disability based on individualized health and risk factors. Methods: This study analyzes Medicare Part B fee-for-service claims from 2011 to 2016 to assess AWV and seasonal influenza and pneumococcal conjugate vaccinations utilization over time. Results: Utilization of the AWV has increased from 8% of Medicare beneficiaries in 2011 to 19% in 2015. In each year, influenza and PCV13 vaccination rates are higher among those who utilize the benefit. More than one-third (33%) of patients who had an AWV in 2015 received a PCV13 vaccination in that same year, compared to 14% of those who did not. Similarly, the seasonal influenza vaccination rate was 64% among those with an AWV and 44% among those without. Conclusion: The AWV demonstrates promise for improving immunization rates among Medicare beneficiaries particularly at the point of care.